The development and consumer acceptance analysis of chlorella vulgaris infused strawberry honey jam / Nur Aisyah Khairul Annuar ... [et al.] - Khairul Annuar, Nur Aisyah; Rusmidi, Muhamad Helmi Husaini; Abdul Hafid, Sitti Rahma; Aazmi, Mohd Shafiq; Radzun, Khairul Adzfa (UiTM Press, 2022)
Chlorella vulgaris is green microalgae belonging to the phylum Chlorophyta. This microalga is known for its high nutrient content, such as protein, chlorophyll, vitamins, and minerals. Through various research, Chlorella contributed to the enhancement of human health, including becoming an immune booster by increasing the activity of the immune system. In addition, it can act as a functional food that will provide nutritional support for humans. Due to that, Chlorella has been used for various applications in the industry like pharmaceuticals, cosmetics, and food products. However, the microalgae traits of having seafood taste and smell are prominent, resulting in unpalatable food in society. Therefore, this study aims to optimise the C. vulgaris, strawberry jam, and honey concoction in developing a new Chlorella-based confectionery food by examining appearance, texture, taste, and aroma parameters. Box-Behnken Design (BBD) is used to create an experimental design matrix of 15 samples with three factors: Chlorella, honey, and strawberry jam, at three distinct levels. An average score based on the 9-point Hedonic scale for each parameter was obtained from a survey participated by 62 participants and was then investigated using response surface methodology (RSM). The results from RSM analysis showed that weak interactions are reflected in combinations of Chlorella and honey, Chlorella and strawberry, and honey and strawberry. The desirability of jam from the optimisation plot indicated that the optimum levels of the three factors were 1.5 ml C. vulgaris, 3 g honey, and 16.5 g strawberry jam. This study provides an overview of the opportunity to develop new products and improvements to increase consumer acceptability by optimising physical parameters to develop nutritional food.